Bowen's disease in a patient with Primary Sjögren's syndrome: A case report and a review of the literature - Besma Ben Dhaou; Imen Rachdi; Rym Ben Mously; Zohra Aydi; Fatma Daoud; Lilia Baili; Insaf Mokhtar; Fatma Boussema (Wolters Kluwer Medknow Publications, 2015)
A rare case of Bowen's disease (BD) in a patient with Primary Sjögren's syndrome is reported. A 42-year-old woman suffering from Primary Sjögren's syndrome retained on the basis of clinical and serological findings, was admitted 3 years later for genital bleeding. The diagnosis of Bowen's disease was established by clinical and histolopathological examination. Classical association of lymphoma and Sjögren's syndrome is described, but to the best of our knowledge, it is the second report of BD associated to Sjögren's syndrome in published literature. A common physio-pathological etiology cannot be excluded.